Penerapan Model PjBL Berbantuan Media Pembelajaran untuk Meningkatkan kreativitas dan Kerjasama Peserta Didik Kelas V SDN 171 Rejang Lebong - Mezia Rahmadanti; Herman Lusa; Pebrian Tarmizi (Universitas Bengkulu, 2022)
AbstractThis study aims to describe the application of the PjBL model assisted by instructional media, to increase the cooperation and activity of the fifth-grade students of elementary school 171 Rejang Lebong. This research is Classroom Action Research. The subjects in this study were 21 students with 9 boys and 12 girls. The research instrument used in this study was the Observation Sheet. The data analysis technique used is the Observation Sheet using formulas and ranges to determine each category. The results of this study indicate that the PjBL model assisted by learning media increases in cycle I to cycle II. So it can be seen from the increase in creativity in the first cycle 44.34% with a sufficient category, then the increase in the results of the observation of the second cycle was 72.61% in the good category. Meanwhile, the results of the observation of cooperation showed that the results in the first cycle were 48.40%, including in the sufficient category. Then it increased in the second cycle, namely 67.71%, which was included in the good category. Based on this result, the application of the PjBL model assisted by learning media can increase the creativity and cooperation of class V students of SDN 171 Rejang Lebong.Keywords: PjBL Model, Learning Media, Creativity, Cooperation.